THE TAX DEPRECIATION MUDDLE. - Milroy, Robert R.; Istvan, Donald F.; Powell, Ray M. (The Accounting Review, 1961)
Interviews with the top-level financial executives in fifty-one leading corporations have shown them to be seriously concerned with the country's tax depreciation policy. They stress that the administration of the present law by the Internal Revenue Service results in wasteful and annoying haggling over lengths of asset Jives and salvage values. In addition, these executives indicate that adherence to any depreciation method based on historical cost alone fails to adequately meet the problem raised by continuing inflation. However much accountants may desire to restrict depreciation to fixed asset historical cost, the interviews with 150 policy makers have reemphasized management's concern with the problem of replacement of assets in a period of rising prices. Those in management interviewed agreed that, unless a firm has the stability of earnings and credit position which would permit it to acquire or replace plant and equipment by borrowing in perpetuity, funds for replacement and/or betterments can come from only three sources: (1) equity sales; (2) retained earnings (or borrowings, that ultimately must be paid out of retained earnings); and, (3) depreciation accruals. Any long-run augmentation of any one or more of these three sources represents recognized aid in management's solution to the problem of replacement. Concessions in the areas of capital gains and small business benefits were made, at the same time, by these leaders in big business as part of their long-range corporate tax "package." The interviewed executives were in general agreement that favorable depreciation reform is needed for long run modernization and growth of the country's productive machine. An examination of their capital-expenditure decision-making processes has revealed, however, that stimulation is not immediate enough to enable depreciation reform to be used as a tool to fight business cycle recessions. Emphasis was placed on the fact that the results of adequate reform will make themselves felt in the decades which stretch into the future, not in the months immediately following the recognition of a business down-turn. The tax depreciation muddle can only be muddied further by any attempt to use tax depreciation allowances as a means for short-run economic juggling.